The Factors Associated with the Implementation of Integrated Management of Sick Children (IMCI) by Health Workers - Monalisa Lubis, Kristin; Herlina; Fadillah Widyaningsih (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Integrated Management of Childhood Illness (IMCI) is a key strategy in improving the quality of healthcare for sick children, with an approach that includes diagnosis, treatment, and disease prevention. The success of IMCI implementation is highly influenced by various factors related to healthcare workers, such as the availability of resources, training, and organizational support. Research Objectives: This study aims to identify the factors influencing the implementation of IMCI by healthcare workers in primary healthcare facilities, particularly at community health centers (puskesmas). Research Methods: This study employs a quantitative approach with a cross-sectional design. Data were collected through interviews and observations of healthcare workers at several puskesmas implementing IMCI. The analysis was conducted to determine the relationship between factors affecting the implementation of IMCI. Results: The study found that the most influential factors in the implementation of IMCI are the availability of resources, including medicines and medical equipment. Additionally, adequate training for healthcare workers and sufficient organizational support are crucial to ensure effective IMCI implementation. Other factors influencing the implementation include communication among healthcare workers and the involvement of families in the care process of sick children. Conclusion: The factors influencing IMCI implementation should be taken seriously, including enhancing the quality of training, fulfilling resource needs, and strengthening organizational support and communication among healthcare